2013
DOI: 10.1016/j.ijdevneu.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in synaptic efficacy in rat brain slices following extremely low‐frequency magnetic field exposure at embryonic and early postnatal age

Abstract: An earlier study demonstrated changes in synaptic efficacy and seizure susceptibility in adult rat brain slices following extremely low-frequency magnetic field (ELF-MF) exposure. The developing embryonic and early postnatal brain may be even more sensitive to MF exposure. The aim of the present study was to determine the effects of a long-term ELF-MF (0.5 and 3 mT, 50 Hz) exposure on synaptic functions in the developing brain. Rats were treated with chronic exposure to MF during two critical periods of brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…Certainly, many tissues including the brain are sensitive to exogenous magnetic and electromagnetic fields [discussed in [5,6]]. It also appears that fetal or neonatal brains may be particularly sensitive to very low frequency magnetic fields, dependent in part, on which part of the brain is assessed [5], with the hippocampus being one in the rodent brain that exhibits sensitivity [5,7]. However, the effects of prenatal exposure to such fields in somewhat inconsistent in mammals, and variability has been reported [reviewed in [8]].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, many tissues including the brain are sensitive to exogenous magnetic and electromagnetic fields [discussed in [5,6]]. It also appears that fetal or neonatal brains may be particularly sensitive to very low frequency magnetic fields, dependent in part, on which part of the brain is assessed [5], with the hippocampus being one in the rodent brain that exhibits sensitivity [5,7]. However, the effects of prenatal exposure to such fields in somewhat inconsistent in mammals, and variability has been reported [reviewed in [8]].…”
Section: Introductionmentioning
confidence: 99%
“…This represents a source of environmental pollution that may induce a variety of effects in organisms. Among them are changes in excitability and synaptic plasticity [Balassa et al, ], cell morphology [Rauš Balind et al, ], the expression, affinity and density of receptors [Janać et al, ; Li et al, ], and oxidative stress [Jelenković et al, ; Selaković et al, ] in the brain, as well as animal behavior [Szemerszky et al, ; Janać et al, ; Madjid Ansari et al, ]. Cerebral ischemia is a pathophysiological condition induced by restricted blood flow through the brain and is a leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to magnetic fields modulates several processes in a variety of biological preparations. Effects exerted in the nervous system by exposure to static [Prina‐Mello et al, ; Oliviero et al, ] and oscillating [Azanza and Del Moral, ; Balassa et al, ] magnetic fields have been clearly demonstrated. However, results were often inconsistent and in spite of recent efforts [Modolo et al, ], comprehensive mechanisms of magnetic field action have not yet been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations revealed that magnetic fields modulated neuronal activity recorded from brain slices [Wieraszko, ; Wieraszko et al, ; Ahmed and Wieraszko, ; Tokay et al, ; Varro et al, ; Balassa et al, ], and fragments of sciatic nerve [Ahmed and Wieraszko, ]. PMF‐induced amplification of nerve cell activity in hippocampal slices, expressed as an increase in the amplitude of evoked potentials [Wieraszko, ], was correlated to rise in concentration of 3'‐5'‐cyclic adenosine monophosphate (cAMP) [Hogan and Wieraszko, ], and with enhancement of release and uptake of the neurotransmitter, glutamate [Wieraszko ; Wieraszko et al, ; Wieraszko and Ahmed, ].…”
Section: Introductionmentioning
confidence: 99%